Diagnostic performance of Contrast-enhanced CT in Pyrrolizidine Alkaloids-induced Hepatic Sinusoidal Obstructive Syndrome - Kan, Xuefeng (Sci Rep, 2016)
Hepatic sinusoidal obstruction syndrome (HSOS) can be caused by pyrrolizidine alkaloids(PAs)-containing herbals. Since PAs exposure is obscure and clinical presentation of HSOS is unspecific, it is challenge to establish the diagnosis of PAs-induced HSOS. Gynura segetum is one of the most wide-use herbals containing PAs. The aim of our study is to describe the features of contrast-enhanced computed tomography (CT) in gynura segetum-induced HSOS, and then determine diagnostic performance of radiological signs. We retrospectively analyzed medical records and CT images of HSOS patients (71 cases) and the controls (222 cases) enrolled from January 1, 2008, to Oct 31, 2015. The common findings of contrast CT in PAs-induced HSOS included: ascites (100%), hepatomegaly (78.87%), gallbladder wall thickening (86.96%), pleural effusion (70.42%), hepatic vein narrowing (87.32%), patchy liver enhancement (92.96%), and heterogeneous hypoattenuation (100%); of these signs, patchy enhancement and heterogeneous hypoattenuation were valuable features. Then, the result of diagnostic performance demonstrated that contrast CT possessed better performance in diagnosing PAs-induced HSOS compared with various parameters of Seattle criteria. In conclusion, the patients with PAs-induced HSOS display distinct radiologic features at CT-scan, which reveals that contrast-enhanced CT provides an effective noninvasive method for diagnosing PAs-induced HSOS.